Biosurfactant producing bacteria isolated from the Nha Trang beach - Hien, Lai Thuy; Thang, Duong Van; Van, Tran Cam; Hoa, Doan Thai (Academia Journal of Biology, 2015)
In Vietnam, there is rare publication on the biosurfactant production, but the requirements are constantly increasing. In this paper, we show some results on the study of biosurfactant producing bacteria isolated from marine environment and their ability to enhance the crude oil degradation. From Nha trang beach sand samples, 5 biosurfactant producing bacteria strains were isolated. Among them, the strains B303 were the best biosurfactant producer. According to the chemical standard kit API 20NE, this strain was determinated as Pseudomonas aeruginosa. The optimum conditions for the biosurfactant production of this strain and the procedure for the biosurfactant extracting were studied. The results of the biosurfactant B303 UV analysis when this strain was cultivated on olive oil showed that it was similar to rhamnolipid. The biosurfactant produced by the strain B303 had very high activity: its emulsification gained 72.5% and its ability to enhance the crude oil degradation on experimental conditions was higher for six times in comparison with the control.